UK-specific cost-effectiveness of tiotropium + olodaterol fixed-dose combination versus other LAMA + LABA combinations in patients with COPD - Tebboth A; Ternouth A; Gonzalez-Rojas N (Dove Medical Press, 2016)
Abigail Tebboth,1 Andrew Ternouth,1 Nuria Gonzalez-Rojas2 1Boehringer Ingelheim Ltd., Bracknell, UK; 2Boehringer Ingelheim GmBH, Ingelheim, Germany Objective: The aim of this study is to assess the cost-effectiveness of other long-acting muscarinic antagonist + long-acting β2 agonist combinations in comparison with Spiolto® Respimat® (tiotropium + olodaterol fixed-dose combination [FDC]) for maintenance treatment to relieve symptoms in adult patients with chronic obstructive pulmonary disease.Methods: A previously published individual-level Markov model was adapted for the perspective of the UK health care system, in line with recommendations from the National Institute for Health and Care Excellence. Individuals progressed through the model based on their forced expiratory volume in 1 second (FEV1) value at baseline and the post-improvement FEV1 value. Changes in FEV1 were taken from a mixed treatment comparison. Costs were obtained from a published cost-utility analysis of tiotropium in the treatment of chronic obstructive pulmonary disease in the UK. Uncertainty was assessed by deterministic and probabilistic sensitivity analysis.Results: Duaklir® Genuair® (aclidinium bromide + formoterol fumarate FDC) and the free-dose combination of tiotropium + salmeterol were dominated by tiotropium + olodaterol FDC. The quality-adjusted life years and costs were identical for Ultibro® Breezhaler® (indacaterol + glycopyrronium FDC) and Anoro™ Ellipta® (umeclidinium + vilanterol FDC) compared with tiotropium + olodaterol FDC, resulting in identical incremental cost-effectiveness ratios.Conclusion: This analysis shows tiotropium + olodaterol FDC to be a cost-effective option for the maintenance treatment of adults with chronic obstructive pulmonary disease in the UK. Keywords: COPD, economic, cost-effectiveness, tiotropium + olodaterol